The identity of Eritrichium lasiocarpum and lectotypification of Hackelia minima (Boraginaceae) - Hao, Jia-Chen; Wei, Lai; Zhou, Yu; Liu, Quan-Ru (Phytotaxa, 2017)
Eritrichium lasiocarpum W.T.Wang is reduced as a new synonym of E. minimum (Brand) H.Hara, and the basionym of the letter, Hackelia minima Brand is lectotypified.